2010
DOI: 10.1186/1471-2458-10-767
|View full text |Cite
|
Sign up to set email alerts
|

Water and sewage systems, socio-demographics, and duration of residence associated with endemic intestinal infectious diseases: A cohort study

Abstract: BackgroundStudies of water-related gastrointestinal infections are usually directed at outbreaks. Few have examined endemic illness or compared rates across different water supply and sewage disposal systems. We conducted a cohort study of physician visits and hospitalizations for endemic intestinal infectious diseases in a mixed rural and urban community near Vancouver, Canada, with varied and well-characterized water and sewage systems.MethodsCohort members and their disease events were defined via universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…For example, sources show that most (79%) residents in a FHA town drink their tap water (regardless of source) [54]. We were not able to quantify specific exposures such as water ingested and contact with animals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sources show that most (79%) residents in a FHA town drink their tap water (regardless of source) [54]. We were not able to quantify specific exposures such as water ingested and contact with animals.…”
Section: Discussionmentioning
confidence: 99%
“… Daily max and minimum temperature Eisenberg [ 15 ]; 2013 Examine the relationship between cholera and precipitation in Haiti including statistical and dynamic models Cumulative daily totals for precipitation Rain gauges and satellite measurements Statistical modeling Control for seasonality All analysis support a strong positive association between precipitation and cholera incidence in Haiti Quasi-Poisson regression (with nonlinear distributed lag function) Granger Causality Wald Test Case-crossover analysis Dynamic modeling White [ 25 ]; 2009 Association between environmental factors and campylobacter infection Precipitation Readings of relevant weather stations Poisson regression Control for seasonality Weekly incidence was associated with increasing mean temperature. Temperature Time-stratified matched case-crossover analysis No association with precipitation Drayna [ 26 ]; 2010 Association between precipitation and acute gastrointestinal illness in pediatric population Total daily precipitation, extreme considered above a certain percentile Readings of relevant weather stations Autoregressive moving average (ARMA) model Control for seasonality Positive association between precipitation and daily visits Teschke [ 21 ]; 2010 Association between the incidence of intestinal infections and environmental factors Precipitation categories according accumulated millimeters of rain over certain periods Readings of relevant weather stations Logistic regression Season, water supply, water source, disinfection and well depth included as variables The association between incidence of disease and precipitation did not remain when controlling for other variables Water chlorination was associated with reduced physician visits Two water systems with the highest proportion of surface water had increased incidence Private well water and well depth were not associated with increased risk Harper; [ 16 ]; 2011 Association between weather va...…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, surveillance of sanitary risk involves inspection of drinking water systems, the source of the drinking water, activities in the catchment area, transmission infrastructure, treatment plants, storage reservoirs and distribution systems [ 68 ]. A large cohort study in Canada found an association between sewage disposal and endemic infectious intestinal disease [ 70 ]. Research on Water Safety Plans, that incorporate sanitary risk factors, demonstrated positive health impacts on diarrheal disease reduction in Iceland [ 71 ].…”
Section: Water Service Indicatorsmentioning
confidence: 99%